P203 CHALLENGES IN THE MANAGEMENT OF RECTUS MUSCLE HEMATOMA DURING TRIPLE ANTITHROMBOTIC THERAPY IN RECENT ANTERIOR STEMI COMPLICATED BY LEFT ENDOVENTRICULAR THROMBOSIS. (18th May 2022) - Caggiari, L; Pittau, R; Marchetti, M; Tuveri, F; Maiani, S; Perra, F; Utzeri, E; Fazzini, L; Contini, F; Montisci, R
Abstract: A 69–year–old woman suffering from hypercholesterolemia, GERD, was admitted to our department for anterior ST elevation myocardial infarction and was treated with primary PCI and DES on the mid–distal LAD. Dual antiplatelet therapy (DAPT) with ticagrelor and cardioaspirin was started. The pre–discharge echocardiogram (echo) showed the presence of left ventricular thrombus (LVT) and anticoagulant therapy (enoxaparin and warfarin) was started. On the 9th day the patient complained abdominal pain with onset of chills and hyperthermia and was suspected an uro–septic fever. The day after a mass appeared on the right abdominal wall at the site of the enoxaparin injection and abdominal contrast CT showed a mass of inhomogeneous density, actively supplied by the inferior epigastric artery and its terminal branches, indicative of hematoma of the abdominal rectus muscle. Anticoagulant therapy was suspended. Interventional radiologists in consideration of clinical stability and stable Hb value and the absence of the signs of active arterial bleeding on CT have not indicated an urgent endovascular treatment and DAPT with clopidogrel and cardioaspirin was continued. After V days, echo showed persistent pedunculated and mobile LVT and aspirin was therefore suspended and anticoagulant therapy was reintroduced with fondaparinux 2.5 mg daily. After two days, considering the stability of hematoma dimensions and the Hb values but the persistence of the extremely floating LVT, fondaparinux was increased at dose of 5 mg daily. In the following days, echo showed LVT reworking until its complete disappearance. On the 32th day blood test showed significant reduction in Hb values and a contrast CT showed an increase in size of the hematoma and resumption of micro bleeding. Fondaparinux was stopped and the patient was transferred to the interventional radiology center. Angiography highlights point–like spreads of extravascular contrast from branches of the inferior epigastric artery and branches of the external circumflex iliac artery. Embolization was performed. After a close monitoring of the hemoglobin values and of the echo which showed no LVT and recovery of LV function, in consideration of her thrombotic and hemorragic risks, she was discharged with DAPT with clopidogrel and low dose of aspirin. Abdominal wall hematoma may be a rare complication of subcutaneous enoxaparin therapy especially in STEMI patients undergoing also a DAPT therapy.